Halal logistics and supply chain management in Southeast Asia - Nor Aida Abdul Rahman; Azizul Hassan; Mohammad Fakhrulnizam Mohammad (London ; New York : Routledge, Taylor & Francis Group, 2021)
"The concept of Halal defines what adheres to Islamic law and is so comprehensive that it goes beyond food to include processes. The Halal industry has allowed many business firms a competitive advantage and is integral in its support for industries from food, tourism, banking, hospitality to medical. This book gives an overview of what Halal is in logistics and supply chain management and discusses related issues and challenges in Southeast Asia. The book also examines Halal logistics and supply chain in reference to global trends and practices. It attempts to integrate theoretical and methodological aspects of Halal logistics and supply chain study in different geographical areas across industries. This will be a useful reference for those who wish to understand the Halal ecosystem and Halal logistics supply chain development"--
Awareness and Demand of Malaysian Consumers towards Halal Logistics of Meat Products: Issues and Opportunities for Transport and Logistics Industry -- Halal Supply Chain and Halal Logistic of Cold Chain Model in Milk Industry: Evidence from Milk Cooperative in Indonesia -- Knowledge Management Strategy towards the Development of Halal Logistic Industry in Vietnam -- A Conceptual Framework Highlighting Barriers in Cold Chain Management for Halal Food Products in Southeast Asia Countries -- The Premier of Halal Logistics in Brunei Darussalam -- Halal Logistics Policy Development in Indonesia -- The Evolution of Halal Logistics in Malaysia, Thailand, Indonesia, Philippines and Vietnam -- Halal Development in Singapore: Halal Logistics Perspective -- The Development of Halal Logistics in Thailand -- Developing an Integrative Model for Halal Transportation in Malaysia: A Structural Equation Modelling Approach -- The development of Halal Logistics Standards in Southeast Asia: Halal Supply Chain Standards (MS2400) as a Principal Reference -- Halal Integrity, Halal Logistics Service Provider (LSP) -- Training Essentials for Capacity Building in Halal Industry: The Importance of Halal Logistics Training -- Successful Halal Compliance Factors for Air Cargo Warehouse: Warehouse Operator Perspective -- Halal Knowledge Integrity Model (HaKIM) in Intensifying the Integrity of Halal Industry -- Digital Innovation, Halal Industry and the Fourth Industrial Revolution.
Includes bibliographical references and index.
PS-Ashe Enterprise Sdn Bhd/En. Shahruddin Shafri/Ketua Perpustakaan ATMA/NMarina/CIP-12/09/2022
Keywords: Halal food industry -- Southeast Asia; Business -- Religious aspects -- Islam; Business logistics -- Southeast Asia